2015
DOI: 10.1016/j.nanoen.2015.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric property studies on Cu Bi2SeS2 with nano-scale precipitates Bi2S3

Abstract: The microscopic mechanisms for higher thermoelectric performance of cost competitive rock salt compound Bi 2 SeS 2 were investigated. A low doping of Cu as an n-type dopant was conducted in order to optimize the band structure and improve the electrical conductivity. It was revealed that this compound exhibits a Seebeck coefficient higher than 300 μV K À 1 , which sustains above 100 μV K À 1 even with Cu doping, leading to a higher power factor. The microstructural characterizations revealed nano-scale Bi 2 S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…Ternary tetradymites, such as Bi 2 Te 2 S, Bi 2 Te 2 Se, Bi 2 Se 2 Te, and Bi 2 Se 2 S, also crystallize in space group R3m and possess the topological insulator phase [36][37][38][39][40], while other compounds of the Bi 2 X 2 Y family (X , Y = O, S, Se, and Te) can crystallize in different structures. For example, Bi 2 S 2 Se has orthorhombic crystal structure with space group Pnma [41], and the Bi 2 O 2 S crystal has both orthorhombic and tetragonal structures with space group symmetries Pnnm and P4/nmm, respectively [42]. Bi 2 O 2 Se and Bi 2 O 2 Te also present a tetragonal-type lattice but with space group symmetry I4/mmm [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Ternary tetradymites, such as Bi 2 Te 2 S, Bi 2 Te 2 Se, Bi 2 Se 2 Te, and Bi 2 Se 2 S, also crystallize in space group R3m and possess the topological insulator phase [36][37][38][39][40], while other compounds of the Bi 2 X 2 Y family (X , Y = O, S, Se, and Te) can crystallize in different structures. For example, Bi 2 S 2 Se has orthorhombic crystal structure with space group Pnma [41], and the Bi 2 O 2 S crystal has both orthorhombic and tetragonal structures with space group symmetries Pnnm and P4/nmm, respectively [42]. Bi 2 O 2 Se and Bi 2 O 2 Te also present a tetragonal-type lattice but with space group symmetry I4/mmm [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The TE conversion efficiency and performance-price ratios of TE devices developed so far and those under development are insufficient to compete with fossil fuel based energy resources. Some intrinsic issues need to be solved for TE materials design and synthesis, and some of them have been lasting for decades.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Different methodologies have been introduced to get porous thermoelectric materials, and it is observed that obtaining such porous structured materials is not straightforward. [3,5,6] Similarly, phonon scattering can be improved by introducing different types of scattering centres such as nano-microscale precipitates, [7,8] interfaces, [9][10][11] hierarchical designs, [12,13] nanostructuring, [1,14] etc.…”
Section: Introductionmentioning
confidence: 99%